The Tethys (Cismon core) and Pacific (DSDP Site 463) Ocean record of OAE1a: a taxonomic and quantitative analyses of planktonic foraminifera and their biological response across the Selli Level equivalent ... - BARCHETTA, ALESSIA (Universit degli Studi di Milano, 2015)
The early Aptian (121 to 118 million years ago) represents a case history of excess CO2 derived from a major volcanic episode, namely the emplacement of the Ontong Java Plateau. During this time-interval, oceans experienced a global phenomenon of widespread deposition of organic carbon-rich sediments under oxygen-depleted conditions, called the Oceanic Anoxic Event 1a (OAE1a). The sedimentary expression of the OAE1a is represented by the Selli Level, a regional marker-bed identified in the Umbria-Marche area (central Italy) consisting of laminated black shales rich in organic matter and low carbonate content, alternated with radiolarian silts. This thesis is aimed at investigating the OAE1a across the Selli Level equivalents at DSDP Site 463 (Mid-Pacific Mountains) and in the Cismon core (Southern Alps, northern Italy) in order to provide a detailed and quantitative study of the planktonic foraminiferal assemblages, because a quantitative documentation in terms of species composition, variation in shell ...